Neutrophil Functions in Periodontal Homeostasis. (25th February 2016) - Cortés-Vieyra, Ricarda; Rosales, Carlos; Uribe-Querol, Eileen
Abstract : Oral tissues are constantly exposed to damage from the mechanical effort of eating and to microorganisms, mostly bacteria. In healthy gingiva tissue remodeling and a balance between bacteria and innate immune cells are maintained. However, excess of bacteria biofilm (plaque) creates an inflammation state that recruits more immune cells, mainly neutrophils to the gingiva. Neutrophils create a barrier for bacteria to reach inside tissues. When neutrophils are insufficient, bacteria thrive causing more inflammation that has been associated with systemic effects on other conditions such as atherosclerosis, diabetes, and cancer. But paradoxically when neutrophils persist, they can also promote a chronic inflammatory state that leads to periodontitis, a condition that leads to damage of the bone-supporting tissues. In periodontitis, bone loss is a serious complication. How a neutrophil balance is needed for maintaining healthy oral tissues is the focus of this review. We present recent evidence on how alterations in neutrophil number and function can lead to inflammatory bone loss, and how some oral bacteria signal neutrophils to block their antimicrobial functions and promote an inflammatory state. Also, based on this new information, novel therapeutic approaches are discussed.